The political economy of agrarian change : an essay on the green revolution - Griffin, Keith B. (Cambridge, Mass. : Harvard University Press, 1974)
This book is about technical change in the agricultural sector of under developed countries. it is concerned specifically with the economic, social and political implication of introducing new, high yielding variety of rice and wheat in the rural areas of Asia.
Includes bibliographical references and index.
oo 22/10/18
Loans
Keywords: Agriculture and state; Green Revolution; Agriculture